Organizational culture, business-to-business relationships, and interfirm networks - Woodside, Arch G. (Emerald, 2010)
Organizational Culture, Business-to-Business Relationships, and Interfirm Networks provides deep understanding about business-to-business and organizational relationships. Studies in this volume identify real-life relationship paradoxes and explain how firms manage, not solve, these paradoxes. Extended chapter lengths allow for a deeper analysis into the structures and dynamics of business relationships. Two research reports by Sergio Biggemann present three-years of intensive face-to-face data collection on how interfirm relations form, operate, and change; Biggemans reports include unedited direct quotes from suppliers, focal firms, and customers on their interfirm relationshipsthese studies provide a deep understanding of quality relationships. In three separate but related reports Sylvie Laforet shows that making mistakes is inherent in organizational innovationsunderstanding how organizations work through such mistakes is an important key to understanding success versus failure in innovation outcomes. Volume 16 is for readers who want to go deep into how B2B relationships actually work, and frequently, do not work.
Keywords: Business networks.; Strategic alliances (Business); Interorganizational relations.; elektronické knihy; electronic books